ナンキョクサンギョ ハゲギスTrematomus newnesi Boulenger ノ エドウブツ ハッケン ト サイエ コウドウ カイシ ニ サイシテ シカク ノ ハタス ジュウブンナ ヤクワリ - Fanta, Edith; Donatti, Lucelia; Freiberger, Sandra (1999)
P(論文) ノトセニア科に属する南極産魚ハゲギス, Trematomus newnesi BOULENGERの餌動物発見機能を理解するために, 視覚刺激実験を行った。1997-98年夏期に, サウスシェトランド諸島, キングジョージ島, アドミラルティ湾において, 大小21尾ずつの2群, 計42尾を採取した。実験は環境条件制御をした水槽を用いて行った。光条件は22時間の明期, 2時間の暗期とした。視覚刺激の評価をするために, 餌動物として2種の端脚類, Gondogeneia antarcticaとWaldeckia obesa, それにナンキョクオキアミEuphausia superbaを透明な容器に入れた上で, 水槽に入れた。化学的刺激を与えないように, 餌動物を入れた容器の水と魚が入った容器の水との接触が起こらないようにした。各実験とも, 供試魚の42.3%が刺激に対して反応した。端脚類は18cmの距離から, またナンキョクオキアミは22.5cmの距離から発見された。給餌つまり視覚刺激を与えてから, 最初の行動が起こるまでの時間差は17.7秒であり, 刺激は実験時間30分の51.5%の間持続した。30分の観察時間中に端脚類を攻撃したのは平均20.9回で, "いじめ"を完了した回数は平均9回であった。また, ナンキョクオキアミを攻撃したのは平均28.3回で, 平均12.6回が"いじめ"を完了した。最高値は常に実験開始から10分以内で起こった。刺激に対する反応状態は, 実験の前半に有意に高かった。視覚刺激によって引き起こされる一連の能動的行動が明らかになった。ハゲギスの網膜はニューロンと, 餌動物発見の重要な手段となる正確な像を結ばせる4型の光受容細胞からなる複合基質であり, 化学的, 機械的刺激を欠いても, 十分に摂餌行動を惹き起こすことができる。 In order to improve the understanding of food detection mechanisms in the Antarctic nototheniid fish Trematomus newnesi BOULENGER, visual stimulation was tested. During the Antarctic summer of 1997/98,42 individuals, 21 belonging to each of two size classes, were obtained in Admiralty Bay (King George Island, South Shetlands). Fish tests were undertaken in aquaria maintained under controlled environmental conditions and a photoperiod of 22 hours light and 2 hours darkness. For the evaluation of visual stimulation, two species of amphipods, Gondogeneia antarctica and Waldeckia obesa, and the krill Euphausia superba, were offered as prey inside a transparent container in each aquarium. No contact was established between the water with prey and the water with predators, to avoid chemical stimulation. In each test 42.3% of the individuals reacted to the stimulation. Amphipods were detected from a distance of 18cm and krill from 22.5cm. The time lapse between food offer and the first reaction after visual stimulation was 17.7s and the stimulation lasted for 51.5% of the experimental time (30 min). During 30min of observation a mean of 20.9 attacks and 9.0 persecutions were performed against amphipods and 28.3 attacks and 12.6 persecutions ...